Determination of the incidence of Salmonella contamination of eggs being consumed in Shiraz - AA Jamshidi (Babol University of Medical Sciences, 2000)
Objective: This descriptive study was conducted to determine the incidence of salmonella contamination of eggs being consumed in Shiraz. Methods: 500 eggs were selected randomly at different times on a basis of random sampling from four centers of egg distribution in the city. They were examined in microbiology lab for detection of salmonella, proteus and E.coli. Samples from the shell and contents of each of 500 eggs were taken for enrichment and inoculation on suitable selective culture media. Findings: 3 out of 500 eggs were shown to be positive for salmonella (0.6%). Salmonella typhimurium and c2 (Newport) were isolated from shell surfaces of two of the eggs and only one egg carried Sal.typhimurium in its contents. Furthermore, we isolated E.coli from 9% of the eggs (Either from shells or contents) and proteus from 16% of the eggs. Conclusion: The public health implications of salmonella infections through consumption of eggs have been discussed.